Development of software for machine vision by using Microsoft-C Language / Khairudin Mohamed - Mohamed, Khairudin (1994)
The aim of this project is to provide a literature of machine vision application especially in auto inspection and to develop a computer program of each technique used by using Microsoft C Language. The literature describes an overview of machine vision and development in digital imaging technology especially in machine vision auto inspection techniques. There are 3 techniques used, Histogram, Pixel-by-pixel subtraction and Circular background grid. The data processing in the specific machine vision system may be performed by either using hardware or software. Here Data Translation DT2867 hardware board is used to perform the operation results. The integrated function board performs both grabbing and processing the image frame.